Accessibility service providers’ perceptions of college students with autism spectrum disorder - Gelbar, Nicholas; Cascio, Alexandra; Madaus, Joseph; Reis, Sally (Frontiers in Education, 2022)
Increasing numbers of individuals with Autism Spectrum Disorder (ASD) are pursuing postsecondary education opportunities, including college degree programs. Many receive supports and accommodations from their college accessibility service office. In this study, results of an online survey completed by 147 college accessibility services personnel summarized their perceptions of the facilitators and barriers faced by college students with ASD. Descriptive statistics and qualitative coding procedures were utilized to analyze the data. Respondents believed that the most important facilitators of success were the presence of appropriate executive function, social, and self-determination/self-advocacy skills in students, and the absence of these skills was reported as a major barrier to the success of college students with ASD. Respondents also believed that the students’ ability to self-advocate, make independent decisions, self-regulate behaviors, and use appropriate coping and study strategies facilitate the success of college students with ASD. Implications of these findings and suggested directions for future research are offered.